Strategi Kepala Sekolah dalam Pengembangan Kompetensi Pedagogik Guru PAI untuk Meningkatkan Hasil Belajar Siswa - Lutfiatul Fawaida; Agus Joko Purwanto (Jurnal Wahana Literasi Pendidikan, 2026)
The purpose of this study is to find out the principal's strategy in developing the pedagogic competence of PAI teachers to improve student learning outcomes and to find out the supporting and inhibiting factors of PAI teachers' pedagogic competence in improving student learning outcomes. The method used in this study uses a qualitative approach with a library research approach. Data analysis was carried out by reduction, presentation, and conclusion drawing by validating data through source triangulation. The results of the study show that the principal's strategy in developing the pedagogic competence of PAI teachers is the optimal educational goal that requires a teacher strategy in motivating students to learn. In the motivation of students to learn, a teacher must not only use one kind of strategy, but also use several sets of strategies that are most encouraging for the effectiveness of learning.